Internet use and adolescent drinking : Does it matter what young people do online? - Svensson, Robert; Johnson, Björn ; 0000-0002-1601-2706 (Drug And Alcohol Dependence, 2020)
Background In this study we examine whether the association between internet use and drinking could be different for different types of internet activities among adolescents. We also adjust for a number of theoretically relevant factors such as peer influence, unstructured activities, impulsivity and parental monitoring. Method The data are drawn from four cross-sectional surveys from the years 2016–2019 in eight municipalities in southern Sweden. The sample consist of 3733 adolescents in year 9 of compulsory education, aged 14–15. Results The results show that there is an association between internet activities and drinking and that there are differences depending on what young people do online. Self-presentation and online sociality are both positively associated with drinking, whereas news consumption and playing games are negatively associated with drinking. The results also show that the association between the different internet activities and drinking becomes weaker when adjusting for the control variables. Conclusion This study suggests that more research is needed to examine the correlations between different forms of internet activities and drinking among adolescents in more detail.
2025-02-20T06:20:55.754+01:00
Keywords: Drug Abuse and Addiction; Beroendelära och missbruk; Other Legal Research; Annan rättsvetenskaplig forskning; Criminology; Kriminologi